2014
DOI: 10.1586/17474086.2014.892412
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal enuresis in sickle cell disease

Abstract: Nocturnal enuresis is a prevalent and challenging problem in children and young adults with sickle cell disease (SCD). Limited progress has been made in elucidating etiology and pathophysiology of nocturnal enuresis in individuals with SCD. Among adults with SCD ages 18-20 years, approximately 9% report nocturnal enuresis. Nocturnal enuresis contributes to decreased health related quality of life in people with SCD, resulting in low self-esteem and sometimes social isolation. Postulated non-mutually exclusive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…Early studies demonstrated a dose-dependent relationship between concentration of HbS and degree of hyposthenuria, with individuals with hemoglobin SS or Sβ° genotypes (sickle cell anemia, SCA) demonstrating severely impaired concentrating ability (inability to concentrate urine to >450 mOsm/kg with water deprivation) starting in infancy and those with SCT demonstrating a later onset of impairment usually by age 10 [24]. This impaired ability to concentrate urine starting at a young age is thought to relate to the increased prevalence of nocturnal enuresis among children and adolescents with SCD [25], a phenomenon that may persist into adulthood [26]. …”
Section: Epidemiologymentioning
confidence: 99%
“…Early studies demonstrated a dose-dependent relationship between concentration of HbS and degree of hyposthenuria, with individuals with hemoglobin SS or Sβ° genotypes (sickle cell anemia, SCA) demonstrating severely impaired concentrating ability (inability to concentrate urine to >450 mOsm/kg with water deprivation) starting in infancy and those with SCT demonstrating a later onset of impairment usually by age 10 [24]. This impaired ability to concentrate urine starting at a young age is thought to relate to the increased prevalence of nocturnal enuresis among children and adolescents with SCD [25], a phenomenon that may persist into adulthood [26]. …”
Section: Epidemiologymentioning
confidence: 99%
“…It has been estimated that almost 50 % of children with SCD age 5-10 years and approximately 15 % of adolescents with SCD age 16-20 years suffer from nocturnal enuresis (Wolf et al 2014 ). The etiology of this increased prevalence of nocturnal enuresis is likely multifactorial.…”
Section: Genitourinary Complicationsmentioning
confidence: 99%
“…Nocturnal enuresis has been defined as the persistence of urination in the bed (bedwetting) at night, two or more times per week after the age of 5 years, for a period of at least 3 months [10]. It can present as a primary form (no previous dry period) or a secondary form (previous dry period), and as monosymptomatic (absence of daytime symptoms) or non-monosymptomatic (presence of daytime symptoms) [9]. Studies which show that children with SCA have a tendency for nocturnal enuresis more than children with normal hemoglobin however reported different prevalence rates and epidemiologic patterns, depending on study methods and definition criteria ( Table 1).…”
Section: Nocturnal Enuresis In Sca: Epidemiologic Perspectivesmentioning
confidence: 99%
“…There are now several hypotheses on the etiopathogenesis of enuresis in children [9,28,29]. In fact, it is believed that children with SCA may have a tendency to develop nocturnal enuresis because of the common general etiopathogenic factors in childhood, SCA-related etiopathogenic factors or a combination of both [9]. Specifically, the unresolved questions include the following: What is the exact Nocturnal Enuresis in Children with Sickle Cell Anemia DOI: http://dx.doi.org/10.5772/intechopen.81578 role of hyposthenuria in SCA-related nocturnal enuresis?…”
Section: Nocturnal Enuresis In Sca: Hypotheses On Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation